Biocontrol of the Major Plant Pathogen Ralstonia solanacearum in Irrigation Water and Host Plants by Novel Waterborne Lytic Bacteriophages - Álvarez, Belén; López, María M.; Biosca, Elena G. (Frontiers in Microbiology, 2019)
Three new lytic bacteriophages were found to effectively control the pathogen Ralstonia solanacearum, a quarantine bacterium in many countries of the world, causative agent of bacterial wilt, one of the most important vascular plant diseases affecting staple crops. Bacterial wilt management has been extensively carried out in the field with fluctuating effects due to R. solanacearum high pathogenic potential and persistence in natural settings, suggesting the need to find alternative treatments as bacteriophages with specific lytic activity. They can massively multiply and specifically kill their host, being effective without causing an ecological impact, and making their integration in a sustainable agrosystem easier. In this work, three lytic phages were isolated from environmental water from geographically distant regions in Spain, and characterized and tested to determine their efficacy against R. solanacearum. The three phages proved to specifically infect a collection of R. solanacearum strains without affecting non-target environmental bacteria from different sources, and were effective on the pathogen populations within a wide range of conditions comprising environmental values of water temperature, pH, salinity, and lack of aeration found in storage tanks. The three displayed high efficiency in R. solanacearum infection, with reductions of the bacterial populations of several orders in just a few hours, and showed the longest persistence in environmental water reported until now for phages with biocontrol potential, pointing out their suitability for field application through irrigation water. Concerning their biocontrol ability against R. solanacearum in environmental water and host plants, they were effective in reducing high populations of the pathogen in water, and bacterial wilt incidence in planta by watering with either one phage or their combinations in non-sterile environmental conditions. All of them belong to the Podoviridae family and are members of the T7likevirus genus. Evidence provided in this work reveals a good potential of the isolated phages for bacterial wilt biocontrol and their suitability to be effectively used as a valuable strategy within the frame of environmentally friendly and sustainable integrated management programs.